Nouveaux Acteurs Sociaux, Permanence et Renouvellement du Clientélisme Politique en Afrique Sub-saharienne - Jean-François Médard (Cadernos de Estudos Africanos, 2007)
The object of this article is to examine the dynamics and reconfigurations of political clientelism, one of the major characteristics of African political systems. The analysis focuses on the restructuring and adapting of African political systems during the «transitional phase» to multi-party democracies in reaction to the political, social and economic crises and the subsequent emergence of new social actors in the African (political) power structures. The article argues that «democracy» and multipartyism have not contributed to eradicate or mitigate clientelist practices and that most achieved, until now, has been the creation of conditions that favor the renegotiation of clientelist relationships.